Pola Asuh dan Relasi Sosial Remaja Lawan Jenis: Studi Budaya pada Suku Banjar di Desa Jamil - Sumiati; Ni'mah; Riyanti, Ayu (CV Kalimasada Group, 2025)
Social and cultural changes in the modern era have had a significant impact on how parents raise their children, including guiding their interactions with the opposite sex. In the Banjar community, this shift is evident in parenting patterns that are increasingly shifting from traditional parenting based on customary and religious values to more permissive parenting. This encourages adolescents to freely establish social relationships with the opposite sex, without adequate parental control. This study aims to describe parental parenting patterns and their impact on adolescents' social relationships with the opposite sex in Jamil Village, South Labuan Amas District, South Kalimantan. The study used descriptive qualitative methods using in-depth interviews, observation, and documentation. The results indicate that permissive parenting is the dominant parenting style, making adolescents more comfortable forming relationships with peers of the opposite sex outside the home than communicating with family. Furthermore, authoritarian parenting patterns were also found, resulting in minimal communication and an increased tendency for adolescents to keep problems to themselves without parental guidance. This change in parenting patterns has implications for a shift in social values in the Banjar community, from a collective parenting style to a more individualistic one. This research is expected to be a reference for families and communities in building balanced parenting patterns so that adolescents can grow with healthier and more controlled social behavior.